(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Geology of an area in the western part of the Monticiano-Roccastrada Range is shown below. Two zones, separated by a normal fault, are distinguished. Upper "Verrucano", Tocchi Fm. and Calcare Cavernoso, building up the western zone, form upright and broad folds. The eastern zone, comprising the Risanguigno Fm. and the "Verrucano s.l." Group (Poggio al Carpino Fm., M.te Quoio Fm. , and Upper Verrucano), shows an east vergent, imbricated structure. In this zone, the Risanguigno Fm. seems to be conformly overlain by the Poggio al Carpino Fm. Constituents and granulometry of a sample of polymict metaconglomerate of the M.te Quoio Fm. are described and two red limestone clasts (samples EH 82-06-1 and EH 82-06-11) have been found within the meta-conglomerates of the M.te Quoio Fm., containing two different bioassociations with fusulinids, Uppermost Carboniferous (Latest Gzhelian)-Early Permian (Asselian) and Early Permian respectively. Identified fusulinids from sample EH 82-06-1 belong to Pseudofusglina ascedens Rauser, Daixina ? sp., Eoparafusulina (E.) cf. ferganensis (Dutkevitch), E. (E.) parasolida (Bensh) and E. (E.) subcylindrica (Bensh) and to Staffella? spp., Schubertella kingi Dunbar & Skinner, Boultonia cf. willsi Lee and Pseudofusulina paragregaria Rauser in sample EH 82-06-11. These fusulinid faunas recognized for the first time in the Apenninic sequences seem to be correlated with Alpine and Russian coeval assemblages and they seem to confirm the previous finding of Parafusulinae by Bodechtel (1964) from the Elba Island.